Proceedings of Loops and Legs in Quantum Field Theory — PoS(LL2014) 2014
DOI: 10.22323/1.211.0049
|View full text |Cite
|
Sign up to set email alerts
|

Feynman integrals via hyperlogarithms

Abstract: This talk summarizes recent developments in the evaluation of Feynman integrals using hyperlogarithms. We discuss extensions of the original method, new results that were obtained with this approach and point out current problems and future directions. Loops and Legs in Quantum Field Theory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
159
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 38 publications
(65 reference statements)
0
159
0
Order By: Relevance
“…[50,[66][67][68][69][70] and references therein. Moreover, their symbolic computation have been recently implemented in computer programs [71,72].…”
Section: Polylogarithms and The Koba-nielsen Factormentioning
confidence: 99%
See 1 more Smart Citation
“…[50,[66][67][68][69][70] and references therein. Moreover, their symbolic computation have been recently implemented in computer programs [71,72].…”
Section: Polylogarithms and The Koba-nielsen Factormentioning
confidence: 99%
“…The same kind of shuffle operations including G(0, 0; z) = 1 2 G(0; z) 2 allows to reduce cases with multiple terminal labels 0 such as G(A, a n−2 , 0, 0; z) with a n−2 = 0 to convergent polylogarithms and polynomials in G(0; z) [69]. Analogous statements based on a regularization prescription for G(z; z) can be made for upper-endpoint divergences in integrals like G(z, z, .…”
Section: G(mentioning
confidence: 99%
“…Graphs which admit such a good order are called linearly reducible and can be computed, order by order in ε, with the algorithm described in [11,21,22] and implemented in [10,49,51]. In [48] it was found that all massless propagators with ≤ 4 loops are indeed linearly reducible, and the same method was even applied to some 6-loop p-integrals [49,50]. The remaining challenge to the straightforward application of parametric integration in the linearly reducible case is the presence of subdivergences.…”
Section: Pos(ll2016)038mentioning
confidence: 99%
“…Instead, in this paper we present a simple new approach based on parametric integration using hyperlogarithms [21,22,49] which allows us to compute the counterterms of all 6-loop 2-and 4-point graphs analytically, with the sole exception of a single graph which is, however, well-known [20,56,58]. We use the Maple TM implementation HyperInt [51] of this method, which was presented at the preceding conference [50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation